2x + 4 - x = 4x - 5
take all the x terms to the left and the numbered terms to the right, not forgetting to change the 'sign' wen they cross over the = sign
2x - 4x - x = - 5 - 4
add them together, and you get:
-3x = -9
then divide both sides by minus 3
you get
x=3
2007-01-31 06:44:50
·
answer #1
·
answered by Crap_At_Maths 2
·
0⤊
0⤋
x = 3 but by now you have seen this is the answer because I didn't see this question untill I was done answering two others. Well at least I confirmed it for you. and by the way, I came to this conclusion by this means.
2x+4 -x = 4x -5,
x + 4 = 4x - 5,
-3x = -9,
Therefore x = 3
If you are still uncertain then maybe you should ask a math teacher or tutor. Most teachers and tutors like it when someone asks them to explain things like this in my experiance.
Good luck in any case.
2007-01-31 15:44:30
·
answer #2
·
answered by jeff s 2
·
0⤊
0⤋
Ans=3
X+4=4X-5
-3X=-9
X=3
2007-01-31 14:51:17
·
answer #3
·
answered by WS G 1
·
0⤊
0⤋
Whats The Value Of X
2x+4-x=4x-5
If X=1
then 2(1) + 4 -(1) = 4(1)-5
= 2+4-1=4-5
=5=1
Answer Is 5
2007-01-31 14:41:56
·
answer #4
·
answered by blueblood 3
·
0⤊
0⤋
Step 1. Get all of the X's on one side of the equation: 2x - 4x - x = -5 - 4
Step 2. Simplify: -3x = -9
Step 3. Solve for x by dividing by 3: x = 3
2007-01-31 14:41:11
·
answer #5
·
answered by Phil L 1
·
2⤊
0⤋
2x+4-x=4x-5 here is the equation
1x+4=4x-5 reduce 2x-x to 1x
1x-4x=-5-4 bring over 4x, making it a -4x - bring over 4, making it -4
-3x=-9 reduce 1x-4x=3x reduce -5-4=-9
-3x/3=-9/3 sub 3, goes into 3 and 9, do both sides
-x=-3 -3xdivided by 3 is -x,-9 divided by 3 is -3
3=x switch -x to x -3 to 3, the negatives cancel out
2007-01-31 14:47:36
·
answer #6
·
answered by scaffmasterus 3
·
0⤊
0⤋
2x + 4 - x = 4x - 5
x + 4 = 4x - 5
x + 4 - x = 4x - 5 - x
4 = 3x - 5
4 + 5 = 3x - 5 + 5
9 = 3x
9/3 = 3x/3
9/3 = x
3 = x
The answer is x = 3
Insert the x value into the equatin
- - - - - - - - - - - - - - - - - - - - - -
Check
2x +4 - x = 4x - 5
2(3) + 4 - 3 = 4(3) - 5
6 + 4 - 3 = 12 - 5
10 - 3 = 12 - 5
7 = 7
- - - - - - - - - - - -s-
2007-01-31 14:43:44
·
answer #7
·
answered by SAMUEL D 7
·
0⤊
0⤋
Just simple:
Bring all the x's to one side and the numbers to the other:
2x-x-4x=-5-4
-3x=-9
x=3
2007-01-31 14:41:50
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
x=3
2007-01-31 14:39:04
·
answer #9
·
answered by km1735 2
·
1⤊
0⤋
2x+4 -x = 4x -5
1st combine like terms :
x + 4 = 4x - 5
-3x = -9
2ndly isolate the variable with division :
x = 3
2007-01-31 14:43:13
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋